2022
DOI: 10.1101/2022.01.26.477948
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rhythmic Cilium in SCN Neuron is a Gatekeeper for the Intrinsic Circadian Clock

Abstract: The internal circadian rhythm is controlled by the central pacemaker in the hypothalamic suprachiasmatic nucleus (SCN). SCN drives coherent and synchronized circadian oscillations via intercellular coupling, which are resistant to environmental perturbations. Here we report that primary cilium is a critical device for intercellular coupling among SCN neurons and acts as a gatekeeper to maintain the internal clock in mice. A subset of SCN neurons, namely neuromedin S-producing (NMS) neurons, exhibit cilia dynam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 39 publications
1
2
0
Order By: Relevance
“…We were surprised to find that our analysis revealed that MCHR1 ciliary localization remained largely fixed across males and females, upon fasting and diet induced obesity, with only subtle significant changes observed in cilia length. Our observation that ACIII cilia length changes within the SCN depending on the light or dark cycle as recently reported in a pre-print, assured us that our analysis could detect broad scale changes in cilia lengths, frequency and localization (Tu, Li et al 2022). It was interesting that we also detected length changes in cilia with both MCHR1 and ACIII in the shell of the nucleus accumbens at different circadian time points (Becker-Krail, Walker et al 2022).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…We were surprised to find that our analysis revealed that MCHR1 ciliary localization remained largely fixed across males and females, upon fasting and diet induced obesity, with only subtle significant changes observed in cilia length. Our observation that ACIII cilia length changes within the SCN depending on the light or dark cycle as recently reported in a pre-print, assured us that our analysis could detect broad scale changes in cilia lengths, frequency and localization (Tu, Li et al 2022). It was interesting that we also detected length changes in cilia with both MCHR1 and ACIII in the shell of the nucleus accumbens at different circadian time points (Becker-Krail, Walker et al 2022).…”
Section: Discussionsupporting
confidence: 78%
“…To determine if MCHR1 cilia localization changes with the light cycle, we assessed brains at ZT8 (light) and ZT23 (dark). We initially assessed the suprachiasmatic nucleus (SCN), the classic region involved in circadian rhythms and a where cilia length changes have recently cilia been implicated (Hastings, Maywood et al 2018, Tu, Li et al 2022). While we do not observe MCHR1 positive cilia in the SCN, we did note similar changes in ACIII cilia to those observed by Tu et al ( Figure 4A ).…”
Section: Resultsmentioning
confidence: 99%
“…HTR6 transcript levels in the brain oscillate (Baldi et al, 2021). A recent preprint suggested that cilia are essential for the rhythmicity of a subset of neurons in the suprachiasmatic nuclei (Tu et al, 2022). We do not know if 5-HTR6 axo-ciliary synapses oscillate and may be involved in chromatin remodeling during sleep/wake cycles (Hor et al, 2019), which may impact learning and memory (Rasch and Born, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, advanced triplet harvesting method is also an effective approach, which was carried out by using efficient triplet emitters with much shorter triplet lifetime [63] or novel fast triplet-harvesting materials, e.g. TADF emitters [47,48] or other promising candidates [6,64,65]. Inspired by the successful applications of heterojunction device physics in OLEDs and LEDs [66,67], it is highly desired to construct OLEDs with multi-layered architecture [13,68,69].…”
Section: Roll-off Behaviours Of S-oledsmentioning
confidence: 99%
“…high EQE/PE, luminance, device stability etc. Very recently, distinct progress in EL performance has been achieved for either of them [64,65]. High-performance monochromatic and white s-OLEDs will be anticipated by using these novel materials and mechanisms.…”
Section: Unique Challenges For Power-efficient S-oledsmentioning
confidence: 99%